2016
DOI: 10.1080/19345747.2016.1164780
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Effects of a Low-Cost and Large-Scale Summer Reading Intervention on Elementary School Children's Reading Comprehension

Abstract: To improve the reading comprehension outcomes of children in high poverty schools, policymakers need to identify reading interventions that show promise of effectiveness at scale.This study evaluated the effectiveness of a low-cost and large-scale summer reading intervention that provided comprehension lessons at the end of the school year and stimulated home-based summer reading routines with narrative and informational books. We conducted a randomized controlled trial involving 59 elementary schools, 463 cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 41 publications
4
24
0
Order By: Relevance
“…Adherence to the core lesson components was high across both a lesson using a narrative text (lesson 1) and a lesson using an informational text (lesson 4). On average, Core READS teachers implemented 87% of the essential lesson elements, compared with 83% for Adaptive READS teachers, and adherence levels across both schools was comparable to our previous studies (Kim et al., ; White et al., ). High overall adherence may have been due, in part, to the closeness with which most teachers stuck to the lesson scripts, often reading them verbatim.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Adherence to the core lesson components was high across both a lesson using a narrative text (lesson 1) and a lesson using an informational text (lesson 4). On average, Core READS teachers implemented 87% of the essential lesson elements, compared with 83% for Adaptive READS teachers, and adherence levels across both schools was comparable to our previous studies (Kim et al., ; White et al., ). High overall adherence may have been due, in part, to the closeness with which most teachers stuck to the lesson scripts, often reading them verbatim.…”
Section: Resultssupporting
confidence: 85%
“…Importantly, however, teachers in both conditions demonstrated high fidelity to the six READS lessons that previous READS studies have demonstrated are critical to the success of the intervention and are teachers’ primary responsibility in Core READS (Kim & White, ). Although teachers in Adaptive READS schools made some changes to the lessons, they also enacted over 80% of the essential lesson elements, which is comparable to previous READS studies (Kim et al., ). At the same time, there were modest but statistically significant differences suggesting that Adaptive READS teachers taught longer lessons and were less likely to read from the lesson plans.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations